Small Molecule Survivin Inhibitor YM155 Displays Potent Activity Against Human Osteosarcoma Cells. (13th September 2016) - Zhang, Shufeng; Wang, Xiaohui; Gu, Zhimin; Wang, Li
ABSTRACT: Survivin is an important oncogenic protein expressed highly in osteosarcoma. Here, we have shown that small molecule inhibitor YM155 potently suppressed survivin expression, inhibited cell growth, and induced apoptosis in osteosarcoma cells. Furthermore, we also showed that knock down of survivin by small interfering RNA strongly inhibited cell viability in two osteosarcoma cell lines, suggesting that suppression of survivin essentially contributes to YM155-mediated anticancer activity in osteosarcoma cells. Collectively, our study suggests that YM155 holds promise for patients with osteosarcoma.